2020
DOI: 10.1021/acsapm.9b01159
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Polyurethane Sponges with Temperature-Controlled Superwettability for Oil/Water Separation

Abstract: Here we have obtained a thermoresponsive three-dimensional (3D) polyurethane (PU) sponge with temperature-controlled superwettability. First, silanization was used to enhance the surface roughness of the PU sponge and reactive vinyl groups were provided. We then grafted a polyisopropylacrylamide (PNIPAAm) hydrogel to the PU skeleton, resulting in the preparation of a temperature-responsive 3D PU material showing useful oil−water separation performance. The surface morphology, chemical composition, and wettabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…THV investigated in this study showed 38.2, 10.4, and 51.4 mole percentage of VDF, HFP, and TFE, respectively (31). Quantitative analysis of the 19 F NMR spectrum of THV-221 G shows that 50% of TFE units are adjacent to each other, while 90% of HFP groups are closer to VDF units (32). Furthermore, the critical molar mass (M c ) for the entanglement of random branches of THV (having 39% TFE, 11% HFP, and 50% VDF) equals 2.5 times the molar mass of entanglements M e (M c = 2.5 M e ), while M e of THV was determined as 4,100 g/mol (33).…”
Section: Effect Of Applied Voltagementioning
confidence: 73%
See 2 more Smart Citations
“…THV investigated in this study showed 38.2, 10.4, and 51.4 mole percentage of VDF, HFP, and TFE, respectively (31). Quantitative analysis of the 19 F NMR spectrum of THV-221 G shows that 50% of TFE units are adjacent to each other, while 90% of HFP groups are closer to VDF units (32). Furthermore, the critical molar mass (M c ) for the entanglement of random branches of THV (having 39% TFE, 11% HFP, and 50% VDF) equals 2.5 times the molar mass of entanglements M e (M c = 2.5 M e ), while M e of THV was determined as 4,100 g/mol (33).…”
Section: Effect Of Applied Voltagementioning
confidence: 73%
“…Materials with hydrophobic and oleophilic characters have potential to be used in processing the oil/water separation due to oil spills, an important environmental issue (15). In this regard, we need to mention that recently oil spills result in severe economic and environmental problems (16)(17)(18)(19). Moreover, the oil containing wastewater in the routine life is a big scientific challenge because of additional contaminants such as heavy metals and organic dyes (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of molecular entities incorporated into these polymers and responsible for stimuli‐responsive characteristics are summarized in Figure . Due to technological importance of particular interest are responses to pH, [ 1–5 ] temperature, [ 6–14 ] H 2 O, [ 15–21 ] redox agents, [ 22–28 ] CO 2 , [ 29–34 ] glucose, [ 35 ] enzyme, [ 36–38 ] electric [ 39 ] and/or magnetic field, [ 40–42 ] electromagnetic radiation, [ 43,44 ] and mechanical forces [ 45–48 ] which are discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The filtration method is suitable for industrial oil/water separation settings because it allows a higher flux than the absorption method [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Since absorbents can be simply placed on oil spill sites and oil can be easily removed in situ by absorbents, the absorption method is more practical than the filtration method in cases of oil spill accidents [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. For oil/water separation, a good absorbent should satisfy the following criteria [ 29 , 30 ]: (i) the absorbent should possess superhydrophobic and superoleophilic characteristics to selectively absorb oil from an oil/water mixture and (ii) the absorbent should possess a high specific surface area to absorb a large amount of oil.…”
Section: Introductionmentioning
confidence: 99%